O PRINCÍPIO DA DIGNIDADE DA PESSOA HUMANA - Rosa Maria Guimarães Alves (Universidade do Oeste Paulista, 2009)
This article deals with the principle of human dignity. It should be clarified that it stemmed from an insight lived on the campus of the University, revealed that the appropriateness of the conception study of the ontological principle of human dignity. Therefore the text, at its beginning, is permeated with philosophical aspects, trying to demonstrate that the principle in question is suitable for the conception and axiological metaphysics. Then, there is reference to human rights and it seeks to deepen the concept of human dignity on the ontological aspect, to finally see it as a principle to be applied in the legal field.